Internet connectivity disruption in Rwanda (Rwanda) - Voidly (2026)
CRITICAL severity disruption detected in Rwanda. Confidence: 65%. Data sourced from IODA.
Network Disruption Incident ID: RW-2026-0005
Keywords: internet disruption; RW; disruption; critical